Innovation at the base of provider’s relationships - Alania Vera, Enrique (2017)
The innovation does not have a model or path previously defined so it is possible to promote the innovation since the demand so a key factor is the big buyer. For this purpose, it is important to generate an environment of collaboration between customers and suppliers. It is relevant to understand the mechanism to do contracts so the key customer could be promote new ideas to solve operating problems and at the same time increase the competitive position of supplier, customer and the country.